Uric acid excretion in healthy subjects: a nomogram to assess the mechanisms underlying purine metabolic disorders - Puig, Juan G.; Torres, Rosa J.; de Miguel, Eugenio; Sánchez, Arantxa; Bailén, Rebeca; Banegas, José R. (Metabolism, clinical and experimental, 2012)
The reference range for urinary uric acid excretion has not been precisely defined. Different urinary variables have been proposed to determine the renal contribution to increased or decreased serum urate concentrations. We examined which urinary variable best indicates uric acid excretion over a wide range of serum urate concentrations. Purine metabolism was studied in 10 healthy male subjects (aged 26-58 years) both at their endogenous normal serum urate levels (normouricemic state) and after the oral administration of allopurinol (300 mg/24 h for 5 days) and ribonucleic acid (4 g/8 h for 4 days) to decrease (hypouricemic state) and increase (hyperuricemic state) serum urate concentrations, respectively. The results from patients with several conditions known to affect uric acid synthesis and/or the renal excretion of uric acid were used to validate a constructed nomogram. Over a wide range of mean serum urate levels (from 2.7 to 9.5 mg/dL) and mean 24-hour urinary uric acid excretion (171 to 1368 mg/[24 h 1.73 m2]), the highest correlation coefficient between serum urate and uric acid excretion was obtained for the 24-hour uric acid determination (r = 0.928; P < .001). The constructed nomogram allowed the definition of the mechanism underlying hyperuricemia and hypouricemia in patients with a myriad of diseases known to affect purine metabolism. The urinary variable that best correlates with a wide range of serum urate concentrations is 24-hour urinary uric acid excretion. The constructed nomogram allows the identification of the kidney contribution to a given purine metabolic abnormality.